A secure lattice-based anonymous authentication scheme for VANETs. (2nd January 2019) - Liu, Hui; Sun, Yining; Xu, Yan; Xu, Rui; Wei, Zhuo
ABSTRACT: Intelligent transportation systems (ITS) can improve the efficiency and safety of transportation. Vehicular Ad Hoc Networks (VANETs) are an important foundation of ITS. However, before being deployed on a large scale, VANETs should resolve the security and privacy issues generated from wireless communication. Digital signature has been used in VANETs to construct anonymous authentication schemes which can realize authentication and privacy preservation. Many previous anonymous authentication schemes have preloaded the master private key into a tamper-proof devices (TPD) which generate the pseudo identity and signature for each vehicle. However, tamper-proof devices cannot defend against side channel attacks. In order to realize better security, this paper takes advantage of lattice-based cryptography to design an anonymous authentication scheme without tamper-proof devices, which achieves security and privacy desired by VANETs. Furthermore, the anonymous authentication scheme lattice based also can defend against quantum computer attack. Finally, the security of this lattice-based anonymous authentication scheme is proven.